2008
DOI: 10.1590/s0100-40422008000200027
|View full text |Cite
|
Sign up to set email alerts
|

Comportamento de cristalização de lipídios estruturados por interesterificação química de banha e óleo de soja

Abstract: Recebido em 21/3/07; aceito em 19/7/07; publicado na web em 23/2/08 CRYSTALLIZATION BEHAVIOR OF STRUCTURED LIPIDS BY CHEMICAL INTERESTERIFICATION OF LARD AND SOYBEAN OIL. The aim of this study was to evaluate the crystallization behavior of binary mixtures of lard and soybean oil in different ratios and their respective structured lipids obtained by chemical interesterification. Crystallization kinetics and polarized light microscopy were used to analyze the mixtures before and after interesterification. The a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
4
0
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 23 publications
(34 reference statements)
2
4
0
2
Order By: Relevance
“…According to Figure 1a, the crystal network of LD shortening was composed of a high amount of larger crystals with a lesser amount of smaller crystals in a lacy network. This was in accordance with the findings reported by Silva et al (2008) as well as Campos et al (2002) who reported that pure LD had a granular crystal structure composed of large crystals. According to a number of other reports, the crystal morphology of fats is also influenced by crystallization temperature, cooling rate and velocity of agitation (Campos et al, 2002).…”
Section: Crystal Morphologysupporting
confidence: 93%
See 1 more Smart Citation
“…According to Figure 1a, the crystal network of LD shortening was composed of a high amount of larger crystals with a lesser amount of smaller crystals in a lacy network. This was in accordance with the findings reported by Silva et al (2008) as well as Campos et al (2002) who reported that pure LD had a granular crystal structure composed of large crystals. According to a number of other reports, the crystal morphology of fats is also influenced by crystallization temperature, cooling rate and velocity of agitation (Campos et al, 2002).…”
Section: Crystal Morphologysupporting
confidence: 93%
“…The consistency of the quaternary mixture shortening was the lowest when compared to any other shortening probably due to the highest amount of tri-unsaturated TAGs (34.89%) ( Table 1). This observation was in accordance with Silva et al (2008) who also found that interesterifed fat mixtures with higher amounts of tri-unsaturated TAGs had lower consistency values. According to Haighton's (1959) classification, the yield value of fats between 200-800 gf/cm 2 was categorized as plastic fats that can be spreadable.…”
Section: Consistency Of Shortening By Penetratorsupporting
confidence: 92%
“…After the reaction, however, the curves showed the sigmoid form characteristic of the Avrami model, in which crystallization takes place more slowly 55 . Silva et al 46 also observed a similar effect on isotherms in the interesterification of lard/ soybean oil blends. Table 4 shows the values of τ SFC , SFC max , and the Avrami parameters (and respective coefficients of determination, R 2 ), indicating velocity (k) and mechanism (n) of crystallization, before and after interesterification.…”
Section: Resultsmentioning
confidence: 64%
“…The high standard deviation values for mean crystal diameter, i.e. the high coefficient of variation, are characteristic of crystallized fats when observed using polarized light microscopy 46,47 . The original blends produced spherulite-shaped crystals with maximum diameters from 47.52 to 116.45 μm.…”
Section: Resultsmentioning
confidence: 99%
“…
O comportamento de cristalização de lipídios tem implicações muito importantes, principalmente no processamento industrial de produtos cujas características físicas dependem em grande parte de cristais de gorduras, como chocolates e margarinas, e separação de gorduras específicas a partir de gorduras naturais através do fracionamento (SATO, 2001;SILVA;ESCOBEDO;GIOIELLI, 2008;DÍAZ GAMBOA;GIOIELLI, 2006). A velocidade de formação dos cristais, o crescimento e as transformações polimórficas são importantes para se determinar o processo e as condições de armazenamento de óleos e gorduras (HERRERA et al, 1998).

Para o completo entendimento da reologia de gorduras plásticas, faz-se necessária a caracterização de sua microestrutura, já que gorduras plásticas consistem de uma rede cristalina em uma matriz oleosa contínua (GHOTRA; DYAL; MARANGONI, 1996a).

…”
unclassified